Experimenting With Online Governance - Tchernichovski, Ofer; Frey, Seth; Jacoby, Nori; Conley, Dalton (Frontiers in Human Dynamics, 2021)
To solve the problems they face, online communities adopt comprehensive governance methods including committees, boards, juries, and even more complex institutional logics. Helping these kinds of communities succeed will require categorizing best practices and creating toolboxes that fit the needs of specific communities. Beyond such applied uses, there is also a potential for an institutional logic itself to evolve, taking advantage of feedback provided by the fast pace and large ecosystem of online communication. Here we outline an experimental strategy aiming at guiding and facilitating such an evolution. We first review the impact of recent technologies for efficiently running massive online experiments used for studying collective action. Research in this vein includes attempts to understand how behavior spreads, how cooperation evolves, and how the wisdom of the crowd can be improved. We then present the utility of virtual-world experiments with governance for improving the utility of social feedback. Such experiments can be used for improving community rating systems and monitoring (dashboard) systems. Finally, we present a framework for constructing large-scale experiments entirely in virtual worlds, aimed at capturing the complexity of governance dynamics, to empirically test outcomes of manipulating institutional logic.